Design and fabrication of motorized car jack / Muhammad Irfan Naqiuddin Talib - Talib, Muhammad Irfan Naqiuddin (2023)
Car users nowadays are so busy with their lives that they neglect car care. Many assume that the car does not need to be inspected as long as it can still move and the chances of having a breakdown are likely high. For example, car users who rarely check the tires will cause the car tires to wear. It will be the factor in the occurrence of flat or broken tires even worse which will cause serious accidents. When the situation occurs, they need to change it by using the car jack tool. This is when the real crisis begins because almost 60% of car users don’t even know how to change their tires using the car jack, especially women and elderly people because it requires strength. The purpose of this project is to make a motorized jack that will save time, be low cost from the market and easier to operate, require less human energy and additional work to operate, and most importantly, is safe, reliable, and able to raise and lower the level using a remote. This product focus is for almost every common car that we can see on our roads and the product will be able to jack cars up to 1.5 Ton.